Ileal Trichobezoar Causing Small Intestinal Obstruction: A Rare Variant - Rai, Binod Kumar; Alam, MD Shahid; Dangol, Elina; Karki, Rishi; Singh, K N (Med Phoenix, 2020)
Bezoars are conglomerate mass of ingested foreign material commonly found in stomach and small intestine in patients with psychiatric problems. On the basis of composition bezoars are classified into many variants. Trichobezoar and phytobezoar are most common composed of hair and fibers of fruits and vegetables, respectively. Bezoar itself is a rare entity and the bezoar solely present in small intestine causing intestinal obstruction is rarer, so we present a case report of 7 years old girl presented in our emergency with the feature of intestinal obstruction. Diagnosis was made on the basis of clinical examination, x-ray finding and history of trichophagia. On exploratory laparotomy the cause of obstruction was found to be ileal trichobezoar.